A novel compound cleaning solution for benzotriazole removal after copper CMP*Project supported by the Special Project Items No.2 in National Long-Term Technology Development Plan, China (Nos. 2009ZX02308-003, 2014ZX02301003-007). (October 2015) - Gu 顾, Zhangbing 张冰; Liu 刘, Yuling 玉岭; Gao 高, Baohong 宝红; Wang 王, Chenwei 辰伟; Deng 邓, Haiwen 海文
Abstract: After the chemical mechanical planarization (CMP) process, the copper surface is contaminated by a mass of particles (e.g. silica) and organic residues (e.g. benzotriazole), which could do great harm to the integrated circuit, so post-CMP cleaning is essential. In particular, benzotriazole (BTA) forms a layer of Cu-BTA film with copper on the surface, which leads to a hydrophobic surface of copper. So an effective cleaning solution is needed to remove BTA from the copper surface. In this work, a new compound cleaning solution is designed to solve two major problems caused by BTA: one is removing BTA and the other is copper surface corrosion that is caused by the cleaning solution. The cleaning solution is formed of alkaline chelating agent (FA/O II type), which is used to remove BTA, and a surfactant (FA/O I type), which is used as a corrosion inhibitor. BTA removal is characterized by contact angle measurements and electrochemical techniques. The inhibiting corrosion ability of the surfactant is also characterized by electrochemical techniques. The proposed compound cleaning solution shows advantages in removing BTA without corroding the copper surface.